Dacryocystectomy: Indications and Results at Tertiary Eye Hospital in Central Saudi Arabia - Galindo-Ferreiro, Alicia; Dufaileej, Mohammed; Galvez-Ruiz, Alberto; Khandekar, Rajiv; Schellini, Silvana A. [UNESP] (Taylor & Francis Inc, 2018)
Purpose: To report indications and success rates of dacryocystectomy (DCT) in a tertiary hospital. Methods: A retrospective chart review was performed of all patients who underwent DCT at the King Khaled Eye Specialist Hospital, Saudi Arabia, from 2008 to 2015. Data included patient demographics, symptoms before and after surgery, and complications. Univariate analysis using parametric and non-parametric methods was performed. Results: Forty-seven DCT surgeries were performed over the study period. The median age of patients was 58.2 +/- 2 years old, 63.8% were female, 60% of surgeries were performed on the left side, and 8% of patients underwent bilateral simultaneous DCT. Chronic dacryocystitis was the surgical indication for DCT for all of the patients and 23.5% of them had dry eye preoperatively. Successful treatment was observed in 80.8% of patients and 8.5% complained of tearing after DCT. Conclusion: The main indication for DCT in our hospital was chronic dacryocystitis with good outcomes for elderly patients with dry eyes.
Keywords: Chronic dacryocystitis; dacryocystectomy; lacrimal sac removal; success rate; surgery indication